Analysis of the Influence of Product Prices and Services on Purchasing Decisions (Study at Indomaret Raung Kediri) - Susetyo, Rahmad Try; Djunaedi, Djunaedi; Rahayu, Budi (Journal of Social Innovation and Business, 2025)
This study aims to determine the effect of price, product and service on purchasing decisions at Indomaret Raung Kediri. This study uses a quantitative research method because the research data is in the form of numbers and is analyzed using statistics and has met scientific principles, namely concrete, objective, measurable, rational, and systematic. The population in this study were all consumers or customers at Indomaret Raung Kediri. The sample in this study was 100 people/respondents. The data collection method used the questionnaire method and library research. While the data analysis method with validity and reliability tests, classical assumption tests, multiple linear regression tests, partial significance tests (statistical t tests), simultaneous significance tests (statistical f tests), and coefficient of determination. From the results of this study it can be concluded that: (1) The price variable has a positive effect on purchasing decisions. This happens because consumers feel that the price at Indomaret Raung Kediri is affordable and in accordance with the benefits and quality received. (2) The product variable has a positive effect on purchasing decisions. This is because the products at Indomaret Raung Kediri are good and of high quality. (3) Service variables do not affect purchasing decisions. This is because customers do not pay much attention to the service provided. (4) Price and product variables together affect purchasing decisions. This is because the pricing is affordable for consumers and the products offered to consumers are good and free from defects.